Тактична розвідка загроз в умовах кібер війни - Пічієнко, М. Г. (ХНУРЕ, 2024)
The thesis discusses the effective protection of organisations against digital threats, in particular in the context of cyber warfare and cyber threats affecting Ukrainian companies. The document emphasises the importance of tac-tical threat intelligence and a system of general threat intelligence to prevent and mitigate cyber attacks. The document also discusses the low level of threat intelligence use in Ukrainian organisations due to low awareness, lack of maturity, lack of a comprehensive approach and insufficient community interaction.
Keywords: тактична розвідка; кібер війна